Context Recollection and False Memory of Critical Lures in the Deese/Roediger-McDermott Paradigm: The Role of Encoding- and Retrieval-Based Mechanisms - Marek Nieznański (Psychological Topics, 2018)
We examined the role of context memory for false recognition of critical lures and for illusory recollection of context in the Deese/Roediger-McDermott paradigm. In order to manipulate context (colour) memory, we asked the participants to read vs. generate items during the study and we presented items from one list using blocked- or mixed-colour formats. Both manipulations confirmed its influence on colour identification. Using signal detection analyses, we estimated memory sensitivity and response bias parameters, assuming that the former reflects encodingmechanism influences, whereas the latter reflects retrieval-based mechanism effects. Our results showed no evidence for diagnostic monitoring, that is, the participants did not use failure of colour recollection as a retrieval strategy for lures rejection. However, we also showed that in the blockedcolour condition, the better memory for targets colours was related to a better gist memory and a stronger proneness to attribute the list-colour to corresponding critical lures. We interpret these results as indicating that participants "misbind" contextual details to activated critical lures at encoding and/or "borrow" these details at retrieval to corroborate the strong familiarity of critical lures.